Solubility, porosity and fluid uptake of calcium silicate-based cements - Esteves Torres, Fernanda Ferrari [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Bosso-Martelo, Roberta; Chavez-Andrade, Gisselle Moraima [UNESP]; Tanomaru-Filho, Mario [UNESP] (Univ Sao Paulo Fac Odontologia Bauru, 2018)
Objective: To evaluate the absorption/fluid uptake, solubility and porosity of White mineral trioxide aggregate (MTA) Angelus, Biodentine (BIO), and zinc oxide-eugenol (ZOE). Material and Methods: Solubility was evaluated after immersion in distilled water for 7 and 30 days. Porosity was evaluated using digital inverted microscope, scanning electron microscope (SEM) and micro-computed tomography (micro-CT). For the fluid uptake test, specimens were immersed in Hank's balanced salt solution (HBSS) for 1, 7, 14 and 28 days. Fluid absorption, solubility and porosity of the materials were measured after each period. Statistical evaluation was performed using one-way analysis of variance (ANOVA) and Tukey tests, with a significance level at 5%. Results: After 7 and 30 days, BIO showed the highest solubility (p<0.05). All methods demonstrated that MTA had total porosity higher than BIO and ZOE (p<0.05). Micro-CT analysis showed that MTA had the highest porosity at the initial period, after its setting time (p<0.05). After 7 and 30 days, ZOE had porosity lower than MTA and BIO (p<0.05). Absorption was similar among the materials (p>0.05), and higher fluid uptake and solubility were observed for MTA in the fluid uptake test (p<0.05). Conclusions: BIO had the highest solubility in the conventional test and MTA had higher porosity and fluid uptake. ZOE had lower values of solubility, porosity and fluid uptake. Solubility, porosity and fluid uptake are related, and the tests used provided complementary data.
Keywords: Physical and chemical properties; Porosity; Solubility; X-Ray microtomography